PENGARUH PEMBELAJARAN AKUNTANSI BERBASIS SAK IFRS DAN SELF-EFFICACY TERHADAP KESIAPAN MAHASISWA MENJADI GURU AKUNTANSI - Raeni, Raeni; Purnami, Rizki Yuli (Dinamika Pendidikan, 2013)
The research was inspired by studentsâ readiness to be Accounting teachers with the rapid progress of science and technology and also free-market for workers. The objective of the study was to test the influence of Accounting learning based on SAK IFRS and self-efficacy toward studentsâ readiness to be Accounting teachers. The population of the research were Accounting education students in classess of 2010 until 2012. Thus, it used proportionate stratified random sampling. The respondents were 85 students in class 2010, 123 students in class 2011 and 154 students in class 2012. Then, the data were analyzed by percentage descriptive and doubled linear regression. The result of regression analysis showed that 1) Accounting learning based on SAK IFRS and self-efficacy contibuted positively and significantly for 52.4% toward studentsâ readiness to be Accounting students, 2) there was a positive and significant influence of Accounting learning based on SAK IFRS for 26.2% toward studentsâ readiness to be Accounting teachers, 3) there was a positive and significant influence of self-efficacy for 16.32% toward studentsâ readiness to be Accounting teachers. The familiarity level for learning Accounting based on SAK IFRS was high with the progress of science and technology and also full adoption from IFRS.